Cutaneous involvement in angioimmunoblastic T-cell lymphoma - Papadavid Evangelia; Panayiotides Ioannis; Dalamaga Marianna; Katoulis Alexandros; Economopoulos Theofanis; Stavrianeas Nikolaos (Wolters Kluwer Medknow Publications, 2010)
Angioimmunoblastic T-cell lymphoma (AITL) is an aggressive non-Hodgkin′s nodal peripheral T-cell lymphoma characterized by general lymphadenopathy, night sweats, fever, hepatosplenomegaly, polyclonal hypergammaglobulinemia, and cutaneous involvement. We present a rare case of AITL cutaneous involvement mimicking toxic erythema recurring with AITL relapse and suggesting a precursor of disease progression.